A Muamalah Fiqh Perspective on the Sale of Zakat Fitrah Rice According to Imam An-Nawawi - Azhari, Nur Fahmi (ABHATS: Jurnal Islam Ulil Albab, 2025)
Zakat fitrah is a personal obligation for every Muslim, performed at the end of Ramadan to purify the soul and assist the needy. In Indonesia, zakat fitrah is commonly given in the form of rice, reflecting the local staple food. However, issues arise when zakat administrators (amil) sell rice donated by one zakat giver (muzakki) to another muzakki without the original owner's consent. This practice, often repeated as part of zakat distribution mechanisms by some institutions, raises legal concerns. This study explores Imam An-Nawawi’s perspective on such practices, examining Shariah principles related to ownership rights, sale contracts, and the authority of amil in managing zakat assets. Using a normative approach through library research, the study analyzes Imam An-Nawawi’s key works, Al-Majmūʿ Sharḥ al-Muhadhdhab and Raudhatut Ṭālibīn. The findings indicate that according to Imam An-Nawawi, zakat fitrah remains the property of the muzakki until it is formally transferred to the rightful recipient (mustahiq). Therefore, any sale conducted by amil without consent from the muzakki contradicts Islamic principles of ownership and valid sale contracts. This research contributes to a deeper understanding of the boundaries of amil authority and provides legal clarity on contemporary zakat management practices from a Shafi’i jurisprudence perspective. [Zakat fitrah merupakan kewajiban personal bagi setiap Muslim sebagai bentuk penyucian diri dan solidaritas sosial. Di Indonesia, zakat ini biasanya ditunaikan dalam bentuk beras sesuai dengan makanan pokok masyarakat. Dalam praktiknya, ditemukan fenomena di mana amil zakat menjual beras zakat fitrah dari satu muzakki kepada muzakki lain tanpa izin pemiliknya, sebagai bagian dari mekanisme distribusi zakat. Penelitian ini bertujuan menelaah pandangan Imam An-Nawawi terhadap praktik tersebut, dengan fokus pada konsep kepemilikan, sahnya akad jual beli, dan batasan kewenangan amil. Metode yang digunakan adalah studi pustaka dengan pendekatan normatif terhadap karya-karya Imam An-Nawawi seperti Al-Majmū‘ Syarḥ al-Muhadzdzab dan Raudhatut Ṭālibīn. Hasil kajian menunjukkan bahwa menurut Imam An-Nawawi, harta zakat fitrah tetap menjadi milik muzakki hingga sampai ke tangan mustahik secara sah, sehingga penjualan oleh amil tanpa izin bertentangan dengan prinsip syariah. Temuan ini menegaskan pentingnya menjaga integritas syariah dalam pengelolaan zakat fitrah dan memberikan landasan normatif bagi praktik distribusi zakat di Indonesia.]